Green Purchase Intention Pada Konsumen Nutrifood di Bandung: Peran Environment Concern Dengan Mediasi Green Trust - Dandy Marcelino (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
In recent years, global warming has been the subject of controversy and has also changed the rhythm of conservation on Earth. Based on this phenomenon, it will have an impact on the increasing number of companies in Indonesia that carry "Green Company" program which aims to reduce energy use and factory waste. This research will find how environment concern influence on green trust for Nutrifood Green Companies and how the impact on their green purchase intention for the future consumption. So it is hope, based on the results of this study, corporate management of Nutrifood will focus on environment concern factors to provide environmentally friendly and increase their market share. If the customer is trusted with the performance of green product from a green company, then the customer will most likely be intent to purchase the green product. The research method used in this study was a quantitative method by descriptive-causal approach, with Structural Equation Modeling (SEM) analysis technique using SMART PLS 2.0 software. The sampling method used was the accidental sampling with 400 respondents. The study results showed that contribution of Environment Concern (X) totally influenced which directly affected on Green Trust (Y) was 64,82%. The remaining 35,18% was influenced by other factors that cannot be explained in this study. Meanwhile, the contribution of Environment Concern (X) and Green Trust (Y) simultenously influenced on that directly affected Green Purchase Intention (Z) was 66,58%. The remaining 33,42% was influenced by other factors that cannot be explained in this study.